2016
DOI: 10.1007/s00122-016-2822-z
|View full text |Cite
|
Sign up to set email alerts
|

General and specific combining abilities in a maize (Zea mays L.) test-cross hybrid panel: relative importance of population structure and genetic divergence between parents

Abstract: General and specific combining abilities of maize hybrids between 288 inbred lines and three tester lines were highly related to population structure and genetic distance inferred from SNP data. Many studies have attempted to provide reliable and quick methods to identify promising parental lines and combinations in hybrid breeding programs. Since the 1950s, maize germplasm has been organized into heterotic groups to facilitate the exploitation of heterosis. Molecular markers have proven efficient tools to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 43 publications
8
45
0
1
Order By: Relevance
“…Flint germplasm is available in the ex-PVP panel primarily through Pioneer Hi-Bred International. The Flint heterotic subgroup is complemented in hybrids by the Iodent heterotic subgroup (Larièpe et al, 2017). The true "Flint" seed characteristic has been purged to maintain the dominant, marketdriven dent phenotype.…”
Section: Crop Sciencementioning
confidence: 99%
“…Flint germplasm is available in the ex-PVP panel primarily through Pioneer Hi-Bred International. The Flint heterotic subgroup is complemented in hybrids by the Iodent heterotic subgroup (Larièpe et al, 2017). The true "Flint" seed characteristic has been purged to maintain the dominant, marketdriven dent phenotype.…”
Section: Crop Sciencementioning
confidence: 99%
“…However, Jocić, Miladinović, & Kaya (2015), Jocković et al (2018), and Makanda et al (2014) analyzed gene effects of inbred lines using line x tester method and they showed that non-additive gene effects were more important for seed yield. Larièpe et al (2017) also observed the after that gene component was more important than the additive component in managing seed yield in sunflower. In addition, Saba, Khan, Sadaqat, & Rana (2016) reported the importance of dominant genes for seed yield in this crop.…”
Section: Introductionmentioning
confidence: 82%
“…Our results are in conformity with Su et al [73] who also reported no significant association between genetic distances and SCA in chrysanthemum. However, Tian et al [78], Lariepe et al [44] reported significant correlation between total GD and SCA for length of terminal raceme in rapeseed, for grain yield and plant height in maize, respectively. Thus the association of GD with SCA is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Among different biometrical approaches, line × tester analysis appears to be ideal for estimating GCA effects of lines and testers, SCA effects of cross combinations, and providing information about nature of gene actions [17, 20, 41]. The extent of heterosis has been reported to be vary with mode of reproduction, genetic distance of parents, traits under investigation, developmental stage of plant and prevailing environment [27, 34, 38, 40, 44, 73]. The pair-wise parental genetic distance (GD) has been suggested as a good indicator of per se hybrid performance and recognition of heterotic groups [27, 34, 38, 40, 44, 73].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation